Persoalan Hukum Penyelesaian Hak atas Tanah dan Lingkungan Berdasarkan Perubahan Undang-Undang Minerba - Wahyu Nugroho (Jurnal Hukum IUS QUIA IUSTUM, 2020)
Law Number 3 of 2020 on Amendments to Law Number 4 of 2009 on Mineral and Coal Mining (Law No.3 of 2020) contains substantial problems. The problems are first, regarding the settlement of land rights for problematic mineral and coal mining business activities, second, regarding the licensing mechanism and environmental supervision of mining areas after Law No. 3 of 2020. The method of thisstudy method is normative legal research with a case approach. The results of his research conclude, first, the settlement of land rights for mining by the central government will obscure the state's function as regulator and licensee; second, mining environmental permits and supervision have not been based on environmental policies, and there is no implementation of an integrated environmental monitoring system in the regions.